PENGEMBANGAN KOMIK SEBAGAI MEDIA PEMBELAJARAN EKONOMI PADA MATERIMANAJEMEN KELAS X SMA MUHAMMADIYAH PEKALONGAN - Eka Ayu Lestari; Triani Ratnawuri (UNIVERSITAS MUHAMMADIYAH METRO, 2020)
Learning media is one of the educational components that is very important for teachers and students in conducting learning activities. Based on interviews with economics teachers and MuhamamdiyahPekalongan high school students, the learning media used are only textbooks or printed books in general without innovation and are less motivating for students in the learning process. So that researchers are interested in developing economic comics in order to attract the attention of students in studying economics and increase student motivation to learn. The aim of this development is to produce a valid and practical economic comic. The model in this study uses the ADDIE model which consists of five stages, namely: Analysis, Design, Development or Production, Implementation or Delivery and Evaluation. The results of the development of economic comics learning media on economic subjects are known to be the recapitulation of assessment results by media experts with an average score of 91% included in the